A method for manufacturing oil well cement using magnesium slag
By using magnesium slag, boehmite and microcrystalline cellulose in oil well cement, the problem of poor anti-seepage performance of oil well cement in high carbon dioxide environment is solved, the impermeability and mechanical properties of the product are improved, and the impermeability and mechanical properties of the product are ensured. Controllability of the preparation process.
Patent Information
- Application Number
- CN202411098572.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-12
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2044-08-12
AI Technical Summary
Oil well cement is difficult to maintain good anti-seepage performance in high carbon dioxide environments, and the existing technology cannot effectively solve this problem.
Magnesium slag is used as raw material, and calcium fluoride is diffused to the internal pores through fine grinding, water soaking, frozen pressing and other processes. Combined with the combination of boehmite and microcrystalline cellulose, the initial mechanical properties and anti-seepage properties are improved.
The excellent anti-seepage and mechanical properties of oil well cement in high carbon dioxide environment are achieved, ensuring the controllability of the cement preparation process and the stability of the product.
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of special cement materials and more specifically relates to a method for manufacturing oil well cement using magnesium slag. Background Art
[0002] Oil well cement is a special cement specially used for cementing projects of oil wells and gas wells. Oil well cement needs to maintain a certain fluidity, pumpability and appropriate thickening time under specific temperature and pressure conditions in the well. In addition, it can solidify quickly after injection into the well and reach a considerable strength in a short period of time. This ensures that after solidification, it can have good impermeability, stability and corrosion resistance to adapt to the complex environment in the oil well, especially the impermeability in a high carbon dioxide environment. Summary of the invention
[0003] The technical problem to be solved by the present invention is how to adapt oil well cement products to a high carbon dioxide environment and maintain good anti-seepage performance during use, and provides a method for manufacturing oil well cement using magnesium slag.
[0004] The purpose of the present invention is to provide a method for manufacturing oil well cement by utilizing magnesium slag.
[0005] The above-mentioned purpose of the present invention is achieved through the following technical solutions:
[0006] A method for manufacturing oil well cement using magnesium slag, the specific manufacturing method comprising:
[0007] Raw materials preparation:
[0008] Take 10-20 parts of magnesium slag, 40-50 parts of limestone, 20-30 parts of clay, and 8-10 parts of iron ore by weight, mix, crush, refine, and sieve to obtain fine abrasive;
[0009] The finely ground material and water are mixed in a mass ratio of 3:1-5:1, and then frozen to obtain a frozen material;
[0010] The frozen material is then freeze-pressed for 10-30 minutes at a temperature below 0°C and a pressure of 10-15MPa, and then the pressed material is dried to remove moisture to obtain a dry pressed material;
[0011] Calcination:
[0012] The dried pressed material is calcined at high temperature and then cooled to obtain a calcined material;
[0013] Grinding:
[0014] The calcined material, retarder and gypsum are mixed, ground and discharged to obtain oil well cement.
[0015] Furthermore, the iron ore is selected from any one of magnetite, hematite and limonite.
[0016] Further, the calcination includes:
[0017] The dried squeezed material is transferred into a cement rotary kiln and calcined at a temperature of 1350-1400°C;
[0018] The residence time of the dried squeezed material in the cement rotary kiln is controlled to be 18-25 minutes; wherein the rotation speed of the cement rotary kiln is 45-50 r / h.
[0019] Furthermore, the magnesium slag includes the following raw materials in parts by weight: 6.5-8.5 parts of CaF2, 45-50 parts of CaO, 2-4 parts of MgO, and 26-30 parts of SiO2.
[0020] Furthermore, the retarder is selected from any one of sodium lignin sulfonate, sodium carboxymethyl cellulose, hydroxyethyl cellulose, sodium ethylenediaminetetramethylenephosphonate, and borax.
[0021] Further, the grinding comprises:
[0022] The calcined material, retarder and gypsum are mixed, and 1-2% of the mass of the calcined material is added with boehmite, and the mixture is ground and discharged to obtain oil well cement;
[0023] The calcined material, the retarder and the gypsum are mixed according to the following weight proportions: 90-100 parts of calcined material, 2-4 parts of retarder, and 8-10 parts of gypsum.
[0024] Furthermore, the grinding also includes, before the grinding begins, adding 0.6-0.8% of the mass of the calcined material, microcrystalline cellulose.
[0025] Furthermore, the grinding also includes, after the grinding, screening to obtain oil well cement with a D50 of 10-15 μm.
[0026] Furthermore, the D50 of the fine abrasive is 40-80 μm.
[0027] An oil well cement is obtained by adopting the above-mentioned manufacturing method.
[0028] Beneficial effects:
[0029] (1) The above technical solution uses magnesium slag as one of the raw materials for oil well cement. The calcium fluoride contained in the magnesium slag can act as a mineralizer and seed in the cement production process. Therefore, adding magnesium slag can be beneficial to the preparation of oil well cement. However, the inventors found that the distribution of calcium fluoride in magnesium slag is relatively dispersed. Even if the theoretical content is in the same range, if it is difficult to diffuse and contact with other raw material components in cement during the cement production process, and only remains inside the magnesium slag, then calcium fluoride is actually difficult to play a role as a mineralizer in the cement preparation process. This will also cause the cement preparation process to become uncontrollable. The inventors grind the raw materials into fine abrasives and soak them in water. Water can penetrate and diffuse into the interior along the pores of the fine abrasives, and because Calcium fluoride in magnesium slag generally has a low solubility in water and is a poorly soluble component. Therefore, calcium fluoride will not be lost due to the use of water, while other water-soluble components or some components that can react with water can be dissolved, further enriching the internal pores, which is conducive to the further penetration and diffusion of water. Combined with freezing, the volume of water will expand in the process of changing from liquid to solid under low temperature conditions, thereby achieving a pore expansion effect. Combined with the subsequent squeezing treatment with a certain pressure, the ice crystals will be broken and the magnesium slag will be broken and refined. In this way, in the subsequent high-temperature calcination process, calcium fluoride is effectively exposed, and the widened pores inside are more conducive to the exchange and contact between substances, so that the residual calcium fluoride inside can fully participate in the reaction;
[0030] (2) The present invention further introduces boehmite and microcrystalline cellulose, and utilizes the combination of the two to work synergistically. The inventors have found that the introduction of boehmite has a good effect on improving the initial mechanical properties of oil well cement. However, due to the complexity of the oil well system, boehmite cannot be added in excess. Excessive addition will affect the product's impermeability. After reducing the amount of boehmite, how to evenly distribute boehmite in the system becomes a new challenge. The oxygen-containing functional groups in the molecular structure of microcrystalline cellulose can form hydrogen bonds with the AlOOH of boehmite in the aqueous cement slurry system. The excellent rheological properties of microcrystalline cellulose to the cement system will assist in the dispersion of boehmite. In addition, the large aspect ratio of microcrystalline cellulose itself makes it easy to form a network structure during the cement hydration process, thereby reducing the sedimentation of boehmite after dispersion. In this way, a relatively excellent comprehensive performance can be achieved with a relatively small amount of boehmite added. DETAILED DESCRIPTION
[0031] The present invention is further described below with reference to specific examples, but the examples do not limit the present invention in any form. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.
[0032] Unless otherwise specified, the reagents and materials used in the following examples are commercially available.
[0033] Example 1
[0034] Raw materials preparation:
[0035] Take 10 parts of magnesium slag, 40 parts of limestone, 20 parts of clay, and 8 parts of iron ore by weight, mix them, pour them into a pulverizer, grind them into fine powder, and sieve them to obtain a fine abrasive with a D50 of 40 μm;
[0036] The magnesium slag includes the following raw materials in parts by weight: 6.5 parts of CaF2, 45 parts of CaO, 2 parts of MgO, and 26 parts of SiO2;
[0037] The iron ore is selected from magnetite;
[0038] The finely ground material and water were mixed at a mass ratio of 3:1, and stirred with a stirrer at a speed of 400 r / min for 60 minutes, and then ultrasonically dispersed at an ultrasonic frequency of 80 kHz for 40 minutes to obtain a dispersion liquid, and then the obtained dispersion liquid was frozen at a temperature of -20°C for 36 hours to obtain a frozen material;
[0039] The frozen material is freeze-pressed for 10 minutes at a temperature below 0°C and a pressure of 10 MPa, and then the squeezed material is vacuum freeze-dried at a vacuum degree of 60 Pa to remove moisture to obtain a dry squeezed material;
[0040] Calcination:
[0041] The dried squeezed material is transferred into a cement rotary kiln and calcined at a temperature of 1350°C;
[0042] The dried squeezed material is controlled to stay in the cement rotary kiln for 18 minutes; wherein the rotation speed of the cement rotary kiln is 45 r / h, and after the calcination is completed, it is naturally cooled to room temperature to obtain the calcined material;
[0043] Grinding:
[0044] 90 parts of calcined material, 2 parts of retarder, and 8 parts of gypsum are weighed respectively by weight, and after the calcined material, retarder and gypsum are mixed, 1% of the mass of the calcined material boehmite and 0.6% of the mass of the calcined material microcrystalline cellulose are added, and the material is ground, discharged, and the material with D50 of 10 μm is sieved to obtain oil well cement;
[0045] The retarder is selected from sodium lignin sulfonate.
[0046] Example 2
[0047] Raw materials preparation:
[0048] Take 15 parts of magnesium slag, 45 parts of limestone, 25 parts of clay, and 9 parts of iron ore by weight, mix them, pour them into a pulverizer, grind them into fine powder, and sieve them to obtain a fine abrasive with a D50 of 60 um;
[0049] The magnesium slag includes the following raw materials in parts by weight: 7.5 parts of CaF2, 48 parts of CaO, 3 parts of MgO, and 28 parts of SiO2;
[0050] The iron ore is selected from hematite;
[0051] The finely ground material and water were mixed at a mass ratio of 4:1, and stirred with a stirrer at a speed of 450 r / min for 70 minutes, and then ultrasonically dispersed at an ultrasonic frequency of 85 kHz for 50 minutes to obtain a dispersion liquid, and then the obtained dispersion liquid was frozen at a temperature of -25°C for 42 hours to obtain a frozen material;
[0052] The frozen material is freeze-pressed for 15 minutes at a temperature below 0°C and a pressure of 12MPa, and then the squeezed material is vacuum freeze-dried at a vacuum degree of 70Pa to remove moisture to obtain a dry squeezed material;
[0053] Calcination:
[0054] The dried squeezed material is transferred into a cement rotary kiln and calcined at a temperature of 1380°C;
[0055] The dried squeezed material is controlled to stay in the cement rotary kiln for 22 minutes; wherein the rotation speed of the cement rotary kiln is 48 r / h, and after the calcination is completed, it is naturally cooled to room temperature to obtain the calcined material;
[0056] Grinding:
[0057] 95 parts of calcined material, 3 parts of retarder, and 9 parts of gypsum are weighed respectively by weight, and after the calcined material, retarder and gypsum are mixed, 1.5% of boehmite by weight of the calcined material and 0.7% of microcrystalline cellulose by weight of the calcined material are added, and the material is ground, discharged, and the material with D50 of 12 μm is sieved to obtain oil well cement;
[0058] The retarder is selected from sodium carboxymethyl cellulose.
[0059] Example 3
[0060] Raw materials preparation:
[0061] Take 20 parts of magnesium slag, 50 parts of limestone, 30 parts of clay, and 10 parts of iron ore by weight, mix them, pour them into a grinder, grind them into fine powder, and sieve them to obtain a fine abrasive with a D50 of 80 um;
[0062] The magnesium slag includes the following raw materials in parts by weight: 8.5 parts of CaF2, 50 parts of CaO, 4 parts of MgO, and 30 parts of SiO2;
[0063] The iron ore is selected from limonite;
[0064] The finely ground material and water were mixed at a mass ratio of 5:1, and stirred with a stirrer at a speed of 500 r / min for 80 minutes, and then ultrasonically dispersed at an ultrasonic frequency of 90 kHz for 60 minutes to obtain a dispersion liquid, and then the obtained dispersion liquid was frozen at a temperature of -30°C for 48 hours to obtain a frozen material;
[0065] The frozen material is freeze-pressed for 30 minutes at a temperature below 0°C and a pressure of 15MPa, and then the squeezed material is vacuum freeze-dried at a vacuum degree of 80Pa to remove moisture to obtain a dry squeezed material;
[0066] Calcination:
[0067] The dried squeezed material is transferred into a cement rotary kiln and calcined at a temperature of 1400°C;
[0068] The dried squeezed material is controlled to stay in the cement rotary kiln for 25 minutes; wherein the rotation speed of the cement rotary kiln is 50 r / h, and after the calcination is completed, it is naturally cooled to room temperature to obtain the calcined material;
[0069] Grinding:
[0070] According to weight, 100 parts of calcined material, 4 parts of retarder, and 10 parts of gypsum are weighed respectively, and after the calcined material, the retarder and the gypsum are mixed, 2% of the mass of the calcined material boehmite and 0.8% of the mass of the calcined material microcrystalline cellulose are added, and the material is ground, discharged, and the material with D50 of 15 μm is sieved to obtain oil well cement;
[0071] The retarder is selected from sodium ethylenediaminetetramethylenephosphonate.
[0072] Example 4
[0073] Compared with Example 1, this example is different in that no microcrystalline cellulose is added, and other conditions remain unchanged.
[0074] Example 5
[0075] The present embodiment differs from the embodiment 1 in that boehmite is not added and the other conditions remain unchanged.
[0076] Example 6
[0077] The present embodiment differs from the embodiment 1 in that microcrystalline cellulose and boehmite are not added, and the other conditions remain unchanged.
[0078] Comparative Example 1
[0079] Compared with Example 1, the difference between this comparative example and Example 1 is that no freezing pressing is performed, and the other conditions remain unchanged, specifically:
[0080] Raw materials preparation:
[0081] Take 10 parts of magnesium slag, 40 parts of limestone, 20 parts of clay, and 8 parts of iron ore by weight, mix them, pour them into a pulverizer, grind them into fine powder, and sieve them to obtain a fine abrasive with a D50 of 40 μm;
[0082] The magnesium slag includes the following raw materials in parts by weight: 6.5 parts of CaF2, 45 parts of CaO, 2 parts of MgO, and 26 parts of SiO2;
[0083] The iron ore is selected from magnetite;
[0084] The finely ground material and water were mixed at a mass ratio of 3:1, and stirred with a stirrer at a speed of 400 r / min for 60 minutes, and then ultrasonically dispersed at an ultrasonic frequency of 80 kHz for 40 minutes to obtain a dispersion liquid, and then the obtained dispersion liquid was frozen at a temperature of -20°C for 36 hours to obtain a frozen material;
[0085] The frozen material is subjected to vacuum freeze drying under a vacuum degree of 60Pa to remove moisture to obtain a dry material;
[0086] Calcination:
[0087] The dried material is transferred into a cement rotary kiln and calcined at a temperature of 1350°C;
[0088] The dried material is controlled to stay in the cement rotary kiln for 18 minutes; wherein the rotation speed of the cement rotary kiln is 45 r / h, and after the calcination is completed, it is naturally cooled to room temperature to obtain the calcined material;
[0089] Grinding:
[0090] 90 parts of calcined material, 2 parts of retarder, and 8 parts of gypsum are weighed respectively by weight, and after the calcined material, retarder and gypsum are mixed, 1% of the mass of the calcined material boehmite and 0.6% of the mass of the calcined material microcrystalline cellulose are added, and the material is ground, discharged, and the material with D50 of 10 μm is sieved to obtain oil well cement;
[0091] The retarder is selected from sodium lignin sulfonate.
[0092] The obtained products of the embodiment and comparative example were subjected to performance tests, and the specific test methods and test results are as follows:
[0093] The products obtained in the above embodiments or comparative examples were made into cement slurry according to a water-cement ratio of 0.45. The specific preparation and curing were carried out in accordance with GB / T 19139-2012 "Test Methods for Oil Well Cement". The cement slurry was poured into a cylindrical mold with a diameter of 12 mm and a height of 25 mm, and then cured for 7 days at a temperature of 90°C and a pressure of 5 MPa, demolded, and then placed in a supercritical carbon dioxide saturated solution in a high-temperature and high-pressure carbon dioxide corrosion instrument for corrosion treatment for 14 days at a temperature of 150°C and a carbon dioxide pressure of 50 MPa;
[0094] Permeability test:
[0095] The samples before and after corrosion were dried at 60°C for 3 days, and the permeability of the samples was tested using a gas permeability automatic tester. The test temperature was room temperature, and the test working medium was nitrogen. The specific test results are shown in Table 1; permeability 1 is before corrosion, and permeability 2 is after corrosion;
[0096] Mechanical properties test:
[0097] According to the standard GB / T 19139-2012 "Test Methods for Oil Well Cement", an electronic hydraulic testing machine with a bearing capacity of 200kN was used to test the compressive strength of the cement before and after corrosion at a load rate of 1200N / s. Three specimens were tested in each group, and the data were averaged. The specific test results are shown in Table 1; compressive strength 1 is before corrosion, and compressive strength 2 is after corrosion;
[0098] Table 1: Product performance test results
[0099] Permeability 1 / % Compressive strength 1 / MPa Permeability 2 / % Compressive strength 2 / MPa Example 1 0.061 38.9 0.068 38.8 Example 2 0.062 38.7 0.070 38.5 Example 3 0.059 39.1 0.069 38.9 Example 4 0.069 36.6 0.081 35.9 Example 5 0.072 35.9 0.086 35.1 Example 6 0.088 34.8 0.101 33.5 Comparative Example 1 0.098 34.2 0.138 32.1
[0100] It can be seen from the test results in Table 1 that the product obtained by the present invention has excellent anti-seepage performance.
[0101] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A method for manufacturing oil well cement using magnesium slag, characterized in that: include: Raw material preparation: by weight, take 10-20 parts of magnesium slag, 40-50 parts of limestone, 20-30 parts of clay, and 8-10 parts of iron ore, mix, crush, refine, and sieve to obtain fine abrasive; The finely ground material and water are mixed in a mass ratio of 3:1-5:1, and then frozen to obtain a frozen material; The frozen material is then freeze-pressed for 10-30 minutes at a temperature below 0°C and a pressure of 10-15MPa, and then the pressed material is dried to remove moisture to obtain a dry pressed material; Calcination: calcining the dried pressed material at high temperature and then cooling it to obtain the calcined material; Grinding: Mix the calcined material, retarder and gypsum, grind and discharge to obtain oil well cement; The grinding comprises: mixing calcined material, retarder and gypsum, adding 1-2% of boehmite by weight of the calcined material, grinding, and discharging to obtain oil well cement; wherein the calcined material, the retarder and the gypsum are prepared according to the following weight proportions: 90-100 parts of calcined material, 2-4 parts of retarder, and 8-10 parts of gypsum; The grinding further comprises: before the grinding begins, adding 0.6-0.8% of the mass of the calcined material with microcrystalline cellulose; after the grinding, sieving to obtain oil well cement with a D50 of 10-15 μm; the D50 of the fine abrasive is 40-80 μm.
2. The method for producing oil well cement using magnesium slag according to claim 1, characterized in that: The iron ore is selected from any one of magnetite, hematite and limonite.
3. The method for producing oil well cement using magnesium slag according to claim 1, characterized in that: The calcination comprises: transferring the dried squeezed material into a cement rotary kiln and calcining it at a temperature of 1350-1400° C.; and controlling the residence time of the dried squeezed material in the cement rotary kiln to be 18-25 minutes; wherein the rotation speed of the cement rotary kiln is 45-50 r / h.
4. The method for producing oil well cement using magnesium slag according to claim 3, characterized in that: The magnesium slag includes the following raw materials in parts by weight: 6.5-8.5 parts of CaF2, 45-50 parts of CaO, 2-4 parts of MgO, and 26-30 parts of SiO2.
5. The method for producing oil well cement using magnesium slag according to claim 1, characterized in that: The retarder is selected from any one of sodium lignin sulfonate, sodium carboxymethyl cellulose, hydroxyethyl cellulose, sodium ethylenediaminetetramethylenephosphonate, and borax.
